Saturn's Northern Auroras and Their Modulation by Rotating Current Systems During Late Northern Spring in Early 2014. Issue 8 (11th August 2018) - Kinrade, J.; Badman, S. V.; Provan, G.; Cowley, S. W. H.; Lamy, L.; Bader, A.
Abstract: The Hubble Space Telescope imaged Saturn's northern ultraviolet auroras during February–June 2014, when Saturn's northern and southern magnetic perturbation fields were locked in antiphase and matched in rotation period (~10.69 hr). During this coalescence period, we test for evidence of rotational modulation of the auroras using the latest rotating current system model and kilometric radio phases derived from Cassini measurements. While we see modulation of auroral intensity in the rotating frames of the planetary period current systems, the pattern is opposite to that expected and is dominated by an asymmetric local time profile that peaks at dawn. Enhancement of the north emission by rotating upward field aligned currents (FACs) is expected to peak at magnetic longitudes of ~90°, whereas here the intensity increased at ~270°. This unexpected finding is attributed to the presence of nonplanetary period oscillation dynamics having affected the auroral morphology, together with insufficient sampling of the rotational system orientations provided during such Hubble Space Telescope campaigns. Rotational modulation is clearest at dawn regardless of the pattern's orientation, suggesting that the physical relationship between rotating FACs and auroral intensity is not direct, having a local time dependence that is not generally observed in the rotating FAC magnitudes. We also find no statistically significant planetary period oscillation of the auroral circle position, but the mean center was offset from the spin pole by ~3° latitude toward early morning local times. Mean auroral boundaries were located at equatorward and poleward colatitudes of 15.0 ± 2.8° and 12.4 ± 3.0°, respectively. Key Points: The 2014 Hubble Space Telescope imagery of Saturn's northern FUV auroras provides updated picture of statistical boundary locations Modulation of auroral intensity by rotating current systems was clearest at dawn local times during the north‐south system coalescence This questions the idea that auroral and SKR emission enhancements simply track the rotating current systems